Research note: the relationship of organizational justice variables with job involvement among southern prison staff - Lambert, Eric G. (Journal of crime and justice, 2019)
There is a growing body of research that has explored how workplace factors affect prison staff, although empirical research specifically aimed at how organizational justice affects correctional job involvement is lacking. This study examined how organizational justice’s two primary dimensions of distributive justice and procedural justice were associated with job involvement, an important work attitude. Self-reported survey data was collected from 322 staff at a large Southern prison. Ordinary least squares regression analysis indicated that both distributive and procedural justice had significant positive associations with job involvement. The results suggest prison administrators need to be aware that organizational justice is important and that improving either distributive or procedural justice should increase job involvement.